RBD decorated PLA nanoparticle admixture with aluminum hydroxide elicit robust and long lasting immune response against SARS-CoV-2 - Meena J.; Singhvi P.; Srichandan S.; Dandotiya J.; Verma J.; Singh M.; Ahuja R.; Panwar N.; Wani T.Q.; Khatri R.; Siddiqui G.; Gupta A.; Samal S.; Panda A.K. (My University, 2025)
Nanoparticles-based multivalent antigen display has the capability of mimicking natural virus infection characteristics, making it useful for eliciting potent long-lasting immune response. Several vaccines are developed against global pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). However these subunit vaccines use mammalian expression system, hence mass production with rapid pace is a bigger challenge. In contrast E. coli based subunit vaccine production circumvents these limitations. The objective of the present investigation was to develop nanoparticle vaccine with multivalent display of receptor binding domain (RBD) of SARS-CoV-2 expressed in E. coli. Results showed that RBD entrapped PLA (Poly lactic acid) nanoparticle in combination with aluminum hydroxide elicited 9-fold higher immune responses as compared to RBD adsorbed aluminum hydroxide, a common adjuvant used for human immunization. It was interesting to note that RBD entrapped PLA nanoparticle with aluminum hydroxide not only generated robust and long-lasting antibody response but also provided Th1 and Th2 balanced immune response. Moreover, challenge with 1 µg of RBD alone was able to generate secondary antibody response, suggesting that immunization with RBD-PLA nanoparticles has the ability to elicit memory antibody against RBD. Plaque assay revealed that the antibody generated using the polymeric formulation was able to neutralize SARS-CoV-2. The RBD entrapped PLA nanoparticles blended with aluminum hydroxide thus has potential to develop asa subunit vaccine against COVID-19. © 2022 Elsevier B.V.